2008
DOI: 10.1177/1356766707087524
|View full text |Cite
|
Sign up to set email alerts
|

A practitioner's report on blogs as a potential source of destination marketing intelligence

Abstract: A primary role of Destination Marketing Organizations (DMOs) is to facilitate industry access to market intelligence and to ensure that operators understand their markets (both existing and emerging). Web logs, or blogs, are a relatively new form of market intelligence arising from peer to peer communication over the internet. The extent to which the content of blogs may augment DMO activities is unknown but is likely to depend on operator predisposition to e-strategies in general. This study reports on a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 13 publications
1
44
0
Order By: Relevance
“…Today, Web 2.0, also referred to as ''Travel 2.0'' in tourism, includes a range of new technological applications such as media and content syndication, mash-ups, AJAX, tagging, wikis, web forums and message boards, customer ratings and evaluation systems, virtual worlds (e.g., Second Life), podcasting, blogs, and online videos (vlogs) (Schmallegger & Carson, 2008). Consumer blogs have emerged as one of the most prominent themes in research on social media in travel and tourism (Braun-LaTour, Grinley, & Loftus, 2006;Mack, Blose, & Pan, 2008;Pan, MacLaurin et al, 2007;Pudliner, 2007;Pü hringer & Taylor, 2008;Waldhö r & Rind, 2008). This research underscores the interest in understanding the functions of blogs in creating and sharing new experiences (Pudliner, 2007), its trustworthiness to online travelers (Mack et al, 2008), as well as the use of it as marketing intelligence (Pü hringer & Taylor, 2008;Waldhö r & Rind, 2008).…”
Section: Social Media On the Internetmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, Web 2.0, also referred to as ''Travel 2.0'' in tourism, includes a range of new technological applications such as media and content syndication, mash-ups, AJAX, tagging, wikis, web forums and message boards, customer ratings and evaluation systems, virtual worlds (e.g., Second Life), podcasting, blogs, and online videos (vlogs) (Schmallegger & Carson, 2008). Consumer blogs have emerged as one of the most prominent themes in research on social media in travel and tourism (Braun-LaTour, Grinley, & Loftus, 2006;Mack, Blose, & Pan, 2008;Pan, MacLaurin et al, 2007;Pudliner, 2007;Pü hringer & Taylor, 2008;Waldhö r & Rind, 2008). This research underscores the interest in understanding the functions of blogs in creating and sharing new experiences (Pudliner, 2007), its trustworthiness to online travelers (Mack et al, 2008), as well as the use of it as marketing intelligence (Pü hringer & Taylor, 2008;Waldhö r & Rind, 2008).…”
Section: Social Media On the Internetmentioning
confidence: 99%
“…Consumer blogs have emerged as one of the most prominent themes in research on social media in travel and tourism (Braun-LaTour, Grinley, & Loftus, 2006;Mack, Blose, & Pan, 2008;Pan, MacLaurin et al, 2007;Pudliner, 2007;Pü hringer & Taylor, 2008;Waldhö r & Rind, 2008). This research underscores the interest in understanding the functions of blogs in creating and sharing new experiences (Pudliner, 2007), its trustworthiness to online travelers (Mack et al, 2008), as well as the use of it as marketing intelligence (Pü hringer & Taylor, 2008;Waldhö r & Rind, 2008). As evidenced by the success of Websites like tripadvisor.com and zagat.com, online travel-related consumer reviews also represent a significant amount of social media for travel purposes (Gretzel & Yoo, 2008;Vermeulen & Seegers, 2008).…”
Section: Social Media On the Internetmentioning
confidence: 99%
“…Tourists who actively participate in SNS are seen as belonging to communities and seem to be socially influenced by other community members [16]. Pühringer and Taylor [27] argue that the intended audiences of tourism blogs and SNS such as Facebook are mainly friends and family members. Thus, the tourists' desire to get social support from SNS can be well understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that this Tourism Created Content is a new form of mediation which is based purely on personal reflections and thus acts as a virtual mediator (Jansson 2002;Munar 2011). Not only do these new user-generated sources of information act as valuable reference points for potential visitors (Liu 2005) they also offer market research to monitor peer-to-peer communication among travellers about their tourism experiences (Park et al 2007;Carson 2008;Pühringer and Taylor 2008;Wenger 2008). These media sources act as ''non-personal mediators for the tourist experience, particularly in the anticipatory and reflective phases (of a tourism experience), (Tussyadiah and Fesenmaier 2009, p 26).…”
Section: Mediation and E-mediationmentioning
confidence: 96%